John W.A. Sanford, The Code of the City of Montgomery, Prepared in Pursuance of an Order of the City Council of Montgomery 7-9, § 6 (1861) - (:unkn) unknown (My University, 1837)
Granted the mayor and aldermen the power and authority to assess, levy, and collect annual taxes on pistol galleries.
Keywords: TAX - PROPERTY OR SALES